Procedural satisfaction matters: Procedural fairness does not ; an experiment studying the effects of procedural judgments on outcome acceptance - Vanessa Mertins (University of Trier, Institute for Labour Law and Industrial Relations in the European Union (IAAEU), 2008)
By reporting data from a laboratory experiment, we provide clear evidence that people value procedures apart from their effects on consequences. We implement a game with one proposer who has distributive power over a pie and four responders who can invest in resistance against the proposer's demand. The proposer is appointed by the use of one of two feasible appointment procedures. We elicit participants' preferences and fairness evaluations over both procedures and study whether responders' resistance against various demands are affected by their procedural judgments. Although the fair process effect, describing the finding that people are more likely to accept outcomes when they feel that they are made via fair procedures, is said to be exceedingly robust, we do not find support for any significant behavioral differences according to people's fairness evaluations. In contrast, we show that procedural satisfaction matters. Surprisingly, responders whose procedural preferences are satisfied offer significantly more resistance than those whose procedural preferences are violated.
Keywords: C72; C91; J52; D23; 330; experiment; fair process effect; frustration effect; procedural fairness; procedural preferences; resistance; threshold public good